A national registry to assess the value of cardiovascular magnetic resonance imaging after primary percutaneous coronary intervention pathway activation: a feasibility cohort study - Jessica M Harris; Rachel C Brierley; Maria Pufulete; Chiara Bucciarelli-Ducci; Elizabeth A Stokes; John P Greenwood; Stephen H Dorman; Richard A Anderson; Chris A Rogers; Sarah Wordsworth; Sunita Berry; Barnaby C Reeves (National Institute for Health Research, 2019)
Background: Cardiovascular magnetic resonance (CMR) is increasingly used in patients who activate the primary percutaneous coronary intervention (PPCI) pathway to assess heart function. It is uncertain whether having CMR influences patient management or the risk of major adverse cardiovascular events in these patients. Objective: To determine whether or not it is feasible to set up a national registry, linking routinely collected data from hospital information systems (HISs), to investigate the role of CMR in patients who activate the PPCI pathway. Design: A feasibility prospective cohort study. Setting: Four 24/7 PPCI hospitals in England and Wales (two with and two without a dedicated CMR facility). Participants: Patients who activated the PPCI pathway and underwent an emergency coronary angiogram. Interventions: CMR either performed or not performed within 10 weeks of the index event. Main outcome measures: A. Feasibility parameters - (1) patient consent implemented at all hospitals, (2) data extracted from more than one HIS and successfully linked for > 90% of consented patients at all four hospitals, (3) HIS data successfully linked with Hospital Episode Statistics (HES) and Patient Episode Database Wales (PEDW) for > 90% of consented patients at all four hospitals and (4) CMR requested and carried out for ≥ 10% of patients activating the PPCI pathway in CMR hospitals. B. Key drivers of cost-effectiveness for CMR (identified from simple cost-effectiveness models) in patients with (1) multivessel disease and (2) unobstructed coronary arteries. C. A change in clinical management arising from having CMR (defined using formal consensus and identified using HES follow-up data in the 12 months after the index event). Results: A. (1) Consent was implemented (for all hospitals, consent rates were 59-74%) and 1670 participants were recruited. (2) Data submission was variable - clinical data available for ≥ 82% of patients across all hospitals, biochemistry and echocardiography (ECHO) data available for ≥ 98%, 34% and 87% of patients in three hospitals and medications data available for 97% of patients in one hospital. (3) HIS data were linked with hospital episode data for 99% of all consented patients. (4) At the two CMR hospitals, 14% and 20% of patients received CMR. B. In both (1) multivessel disease and (2) unobstructed coronary arteries, the difference in quality-adjusted life-years (QALYs) between CMR and no CMR ['current' comparator, stress ECHO and standard ECHO, respectively] was very small [0.0012, 95% confidence interval (CI) -0.0076 to 0.0093 and 0.0005, 95% CI -0.0050 to 0.0077, respectively]. The diagnostic accuracy of the ischaemia tests was the key driver of cost-effectiveness in sensitivity analyses for both patient subgroups. C. There was consensus that CMR leads to clinically important changes in management in five patient subgroups. Some changes in management were successfully identified in hospital episode data (e.g. new diagnoses/procedures, frequency of outpatient episodes related to cardiac events), others were not (e.g. changes in medications, new diagnostic tests). Conclusions: A national registry is not currently feasible. Patients were consented successfully but conventional consent could not be implemented nationally. Linking HIS and hospital episode data was feasible but HIS data were not uniformly available. It is feasible to identify some, but not all, changes in management in the five patient subgroups using hospital episode data. The delay in obtaining hospital episode data influenced the relevance of some of our study objectives. Future work: To test the feasibility of conducting the study using national data sets (e.g. HES, British Cardiovascular Intervention Society audit database, Diagnostic Imaging Dataset, Clinical Practice Research Datalink). Funding: The National Institute for Health Research (NIHR) Health Services and Delivery Research programme. This study was designed and delivered in collaboration with the Clinical Trials and Evaluation Unit, a UK Clinical Research Collaboration-registered clinical trials unit that, as part of the Bristol Trials Centre, is in receipt of NIHR clinical trials unit support funding.